2007
DOI: 10.1590/s1806-83242007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Location and angulation of curvatures of mesiobucal canals of mandibular molars debrided by three endodontic techniques

Abstract: The aim of this study was to assess the correlation between the degree of angulation and the position of root curvatures and their influence on the comparative results between the performances of the Progressive, Staged and Serial Preparation Techniques. The mesiobucal canals of 70 extracted mandibular molars were filled with a radiological contrast of 100% Barium sulphate and radiographed with a direct digital radiographic system, in an apparatus that guarantees that the samples remain in the same spatial pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 6 publications
(5 reference statements)
1
17
0
1
Order By: Relevance
“…In this study it was observed that the wear of the distal wall (Risk Zone) of the mesial canals of mandibular molars was significantly greater than the wear of the mesial wall (Safety Zone) (p<0.05), with no differences between the wear promoted between drills compared. Similar results were observed previously 4 , 6 , 17 . Both GG and TP left an average remaining dentin thickness of approximately 0.6 mm in the distal wall ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study it was observed that the wear of the distal wall (Risk Zone) of the mesial canals of mandibular molars was significantly greater than the wear of the mesial wall (Safety Zone) (p<0.05), with no differences between the wear promoted between drills compared. Similar results were observed previously 4 , 6 , 17 . Both GG and TP left an average remaining dentin thickness of approximately 0.6 mm in the distal wall ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Preflaring of the cervical third decreases the tension of manual and rotary instruments during apical instrumentation by eliminating dentin projections 4 , and also provides greater reliability when defining the working length and the apical gauging 12 . Moreover, when prepares with NiTi instruments without the pre-enlargement in the cervical region with stainless steel instruments, there is a greater action of the NiTi instruments on the wall of the furcation, reducing the dentin thickness to values below 0.5 mm 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preflaring of the cervical third decreases the tension of manual and rotary instruments during apical instrumentation by eliminating dentin projections (13), and also provides greater reliability when defining the working length and the apical gauging (4,5,14). Several methodologies have been employed to assess the effect of endodontic instruments on dentin wall thickness such as: resin blocks (15), scanning electron microscopy (16), radiography (17) and computer tomography (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…É imprescindível que os profissionais que trabalham com Endodontia possuam adequados conhecimentos sobre a anatomia interna dos dentes para permitir o planejamento dos procedimentos endodônticos, que se relacionam com a identificação dos diferentes aspectos observados através de recursos imaginológicos, incluindo as variações anatômicas (MATTUELLA et al, 2005;CONSTANTE et al, 2007a;CONSTANTE et al, 2007b;ESTRELA et al, 2008). O domínio desse conhecimento pode evitar erros durante a identificação, instrumentação e obturação dos canais radiculares (MATTUELLA et al, 2005).…”
Section: Introductionunclassified